(3eYGOf GdPgH aj GdCYjGf GdeTqQaI Hge MdHs - (3CHh GdhaGA GdYQVj , eMeO Hf YeQ Hf YHO GdhgGH GdMdHj GdYQVj,J (B1071 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Pi GdHbGA GdeWdb s
(3BNQgG (B:s
(3jfJgi CKfGA JQLeI GdCejQ CMeO CHj QjTI s
(3GdJQGLe eQJHI Ydi MQha GdeYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B317 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B165s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B292 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B251 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs